Comparison of two methods (visual estimates and filming) for counts of horn flies (Haematobia irritans irritans) (L.) (Diptera : Muscidae) - Lima, LGF; Prado, A. P.; Perri, SHV (Elsevier B.V., 2002)
Visual estimates are generally used for counts of horn flies, Haematobia irritans (L.) and play an important role as an instrument to quantify fly populations in scientific studies. In this study, horn fly counts were performed on 30 Nelore steers in the municipality of Aracatuba, SP Brazil, from January to December 1998. Flies were counted weekly by two methods: the estimate method whereby estimates of the number of flies on one side of the animal are obtained by visual observation, and the filming method whereby images of flies from both sides of the animal are recorded with a video camera. The tape was then played on a videotape recorder coupled to a television and the flies were counted on the screen. Both methods showed variations in horn fly population density during the period studied. However, significant differences (p < 0.05) were observed between the two methods with the filming method permitting the visualization of a larger number of flies than the estimate method. In addition, the filming method permitted safe and reliable counts hours after the images were taken, with the advantage that the tape can serve as an archive for random re-counts. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: Haematobia irritans irritans; estimated visual counts; video recording; populations; comparisons